MINERAL CHEMISTRY AND FORMATION OF AWARUITE AND HEAZLEWOODITE IN THE XEROLIVADO CHROME MINE, VOURINOS, GREECE - Tzamos, E.; Filippidis, A.; Michailidis, K.; Koroneos, A.; Rassios, A.; Grieco, G.; Pedrotti, M.; Stamoulis, K. (Bulletin of the Geological Society of Greece, 2016)
The Serpentinite between the chromite bodies 4 and 5 of Xerolivado mine (Vourinos, Greece), contains sparsely very small grains (<20μm) of awaruite (Fe0.91Cu0.06Co0.03Ni3), heazlewoodite (Ni2.91Fe0.06S2), magnetite and Co pentlandite (Ni3.79Fe2.98Co2.38S8). The olivine contains 0.40 wt% NiO and 6.91 wt% FeO, while the serpentine 0.18 wt% NiO and 3.02 wt% FeO. The Co-content of awaruite is 1.31 wt% and that of heazlewoodite 0.12 wt%. Heazlewoodite is a product of the primary Co-pentlandite reduction, resulting from the serpentinization of the ultramafic rock. The Ni content of awaruite is derived both from olivine and from Co-pentlandite. The reducing environment resulting from serpentinization and the low sulphur fugacity, favour the formation of awaruite, heazlewoodite and magnetite.